2013
DOI: 10.1371/journal.pone.0077428
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion- and Perfusion-Weighted Imaging in Acute Lacunar Infarction: Is There a Mismatch?

Abstract: PurposeCharacterization of lacunar infarction (LI) by use of multimodal MRI including diffusion- and perfusion-weighted imaging (DWI, PWI) is difficult because of the small lesion size. Only a few studies evaluated PWI in LI and the results are inconsistent.MethodsIn 16 LI patients who underwent initial MRI within 6 hours after symptom onset and follow-up MRI within 1 week demographics, clinical presentation, and MRI findings were analyzed with special emphasis on DWI and PWI findings. Time to peak maps were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
(39 reference statements)
0
28
0
Order By: Relevance
“…The results of this study by using whole-brain-coverage CTP are very similar to those of a recent study by using perfusion MR imaging in patients with LI that reported perfusion deficits in 10/16 patients. 14 The sensitivity of whole-brain CTP was much higher than that of NCCT for acute stroke and in particular for LI, and the greater sensitivity of CTP in this study may reflect both whole-brain coverage of perfusion maps and the refinement of current parameters to assess perfusion maps. Studies with negative findings were due to very small lesions that were poorly differentiated from the background, especially in the brain stem; and in a few cases, they were due to poor image quality from movement artifacts.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The results of this study by using whole-brain-coverage CTP are very similar to those of a recent study by using perfusion MR imaging in patients with LI that reported perfusion deficits in 10/16 patients. 14 The sensitivity of whole-brain CTP was much higher than that of NCCT for acute stroke and in particular for LI, and the greater sensitivity of CTP in this study may reflect both whole-brain coverage of perfusion maps and the refinement of current parameters to assess perfusion maps. Studies with negative findings were due to very small lesions that were poorly differentiated from the background, especially in the brain stem; and in a few cases, they were due to poor image quality from movement artifacts.…”
Section: Discussionmentioning
confidence: 64%
“…6 Conflicting results have been reported regarding the presence of perfusion deficits in patients with LI, [7][8][9][10][11] with sensitivities varying from 0% to 68% in studies using MR imaging [12][13][14] and from 17% to 47% with CTP. 15,16 In fact, LI is considered one of the causes of false-negative CTP findings.…”
mentioning
confidence: 99%
“…Previous studies have usually been limited to retrospective data collection and smaller sample sizes. 5,8,[10][11][12]14,16,[27][28][29][30] From our research experience in collecting the acute complications of acute stroke cases, 21 we established detailed definitions and protocols about END and successfully implemented these into our daily clinical practice. When a nursing staff member or duty resident detected END, the information was readily spread via a texting service to the on-duty doctors and attending physicians.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, evidence has accumulated indicating the potential contribution from atherosclerotic processes including the formation of a microatheroma or hemodynamic compromise of an infarction. 14,32 Owing to the two distinct entities of lacunar infarction, 33 SSSIs from atherosclerotic pathologies have been suggested to be larger in size and located in the proximal basal ganglia. 1,34 Our results, in view of the current theory, propose that the biological characteristics of arterial occlusive lesions and the localized parenchymal responses after the occlusion of arterioles would vary according to the nature of the occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation